Using Measurable Indices to Evaluate the Cultural Importance of Socio-religious Plants: Comparative Data from the Three States of India - Kavi K. Oza; Suchitra Chatterjee; Shrey Pandya; Vinay M. Raole (The Ethnobiological Society of Indonesia, 2021)
The aim of the present study is to do the balancing between the science and cultural practices in an increasingly complex developing society and policy on the traditional knowledge landscape. Various quantitative indices are proposed to determine the cultural importance of socio-religious and ethnobotanically valuable plants as a tool for the evaluation of cultural heritage. These indices were applied to an ethnobotanical, sociocultural survey of plants and plant parts traditionally used and consumed in the selected study area. Selected plants were grouped into seven use categories for further analysis. The cultural value index (CV), use value index (UV), the relative frequency of citation (RFC), relative importance (RI), and cultural importance index (CI) were calculated for different plant species cited by 45 informants in different traditional societies from the studied states. The calculated values of the cultural importance of plants through diverse indices generated interesting variations from three regions of India. There were eight common species through all the three states. Among these eight species Butea monosperma shows the highest values from Rajasthan and Ziziphus jujube shows the lowest values from Gujarat region. While Nelumbo nucifera, Vigna mungo, and Nymphaea lotus were also portrayed high calculated values in the CI, RI, and CVs. The combined use of these indices makes it possible to quantify the role which has given to a particular plant within a specific culture in one or many festivals in general or religious rituals.